Asimetri informasi dalam transaksi perbankan syariah di Indonesia - Slamet Haryono (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This study employs the assymmetric information in the Indonesian shariah banking. Assymmetricinformation in the banking sector contains: moral hazard, adverse selection. Moral hazard is a situationin which one agent decides on how much risk to take, while another agent bears (parts of) the negativeconsequences of risky choices. The uncertainty surrounding any bank decisions. The market does notget information about the riskiness of a bank. Asymmetric information problems exist in the bank loanmarket. Depositors cannot distinguish the risk, they deposit their funds in those banks that offer thehighest rates and make the most risky investments. Our result points towards regulator to enhancingtransparency may be useful to reduce incentives for excessive assymmetric information of sharia banking.